2012
DOI: 10.2217/fon.11.148
|View full text |Cite
|
Sign up to set email alerts
|

An Iron Regulatory Gene Signature in Breast Cancer: More than a Prognostic Genetic Profile?

Abstract: Miller LD, Coffman LG, Chou JW et al. An iron regulatory gene signature predicts outcome in breast cancer. Cancer Res. 71(21), 6728-6737 (2011). In breast cancer, recent progress in technology has enabled us to define different prognostic genetic signatures. Based upon them, breast tumors have been grouped into the four principal categories: basal-like or triple-negative, erbB2-positive, normal-like, and luminal type (A and B); with luminal types sharing the expression of estrogen receptor- and/or progesterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Regarding disease pathogenesis and the effects of iron status on breast cancer, which is the focus of the work reported here, a review of the literature revealed that this topic appears to stimulate interest in cycles of roughly 10 years. A previous burst in published activity occurred in the timeframe of 2008–2013 [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The prevailing issues underlying those investigations included the impact of iron deficiency in limiting processes related to tumor development and the effects of excess iron-induced oxidative stress on the carcinogenic process.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding disease pathogenesis and the effects of iron status on breast cancer, which is the focus of the work reported here, a review of the literature revealed that this topic appears to stimulate interest in cycles of roughly 10 years. A previous burst in published activity occurred in the timeframe of 2008–2013 [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The prevailing issues underlying those investigations included the impact of iron deficiency in limiting processes related to tumor development and the effects of excess iron-induced oxidative stress on the carcinogenic process.…”
Section: Introductionmentioning
confidence: 99%